Online Classes in Tribhuvan University: Opportunities and Challenges - Nepal, Arun (Rupantaran: A Multidisciplinary Journal, 2020)
This article aims at identifying the opportunities and the challenges of implementing the online classes in Tribhuvan University (TU) which is the oldest and the largest university in Nepal. The opportunities and challenges have been identified based on the information collected through comparison of the involvement of the students in the face-to-face class before COVID-19 and the online class after the effect of Corona Virus in TU. I have collected the necessary information through naturally occurring environment involving the bachelor level fourth year students who have been studying English education in a TU campus. Although the article discusses some crucial factors that lead to the realization of the need of online class in Nepal, it attempts to justify the emergence of COVID-19 as an opportunity to commence the hot discussion focusing on the need of online classes and its implementation in TU. However, the implementation seems to be more challenging due to some common and hidden problems realized during the implementation of the online class in one of the oldest constituent campuses, i.e. Mahendra Ratna Multiple Campus (MRMC), Ilam. Online classes can be run more successfully if the the common and hidden problems are addressed that have been identified in this article. The article indicates some serious challenges of implementing the online classes in TU; however, online classes can be implemented even in TU more successfully addressing those challenges if the stakeholders take some serious steps to address those challenges.